PENGARUH MEDIA POWERPOINT INTERAKTIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Sindy Oktavia Sugiono Putri; Endang Wahju Andjariani; Budhi Rahayu Sri Wulan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to determine the effect of interactive powerpoint media on students' critical thinking skills. The research used was the quantitative method of one group pretest-posttest with the subject as many as 26 students in grade IV SD Negeri Damarsi Sidoarjo. The research instrument used was in the form of a media and material expert validation sheet, test question sheet, and student response questionnaire sheet. The results stated that the validation of media experts received an average of 90% while the validation of the material expert got an average value of 89% which was categorized as very feasible. The validation of the test questions is declared valid, the multiple choice reliability test gets a value of 645 with a high category while the description of the description gets a value of 621 with a high category. The normality test gets a p-value (0.151) normally distributed. Tcount partial test results (5,959) > Ttable (2,06390), P-Value (0,000) 0.05 so that H0 is rejected. Student responses get a score of 68.84% with a good category, thus interactive PowerPoint media received good responses from students.